Makna Simbolik Ungkapan Tradisional (Tampu Tangari) Pada Masyarakat Kulisusu - Lela Asnia; Asmurti .; Ashar Hasyim (CV. ITTC INDONESIA, 2026)
This research aims to identify the forms and delve into the symbolic meanings of traditional expressions (tampu tangari) within the Kulisusu community in Jampaka Village, Kulisusu District, North Buton Regency, as a means of cultural communication and social control. Employing a descriptive qualitative approach with Roland Barthes' semiotic analysis, this study gathered data through observation, indepth interviews with nine informants, and documentation. The results indicate that tampu tangari manifests as signs constructed through words utilizing natural elements and human anatomy as signifiers. At the denotative level, these expressions carry literal meanings corresponding to the mentioned objects; however, at the connotative level, profound symbolic meanings are found containing moral messages such as praise for work ethics, subtle satire for negative behavior, advice on life wisdom, and an instrument for monitoring behavior to maintain group harmony. Meanwhile, at the myth level, these expressions function as a cultural ideology that naturalizes customary rules into absolute truths collectively believed by the community.